Considering Axiology in the Development of Art - Hamdan Akromullah; Armen Nazaruddin; Miswar Miswar; Kendall Malik; Ferry Fernando; Rica Rian; Elvis Elvis; Rahma Triyana; Jufrinaldi Jufrinaldi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
The rapid advancement of science and technology has produced both significant progress and complex challenges, including value crises, cultural commodification, and dehumanization. In this context, art should be understood not merely as aesthetic expression or a creative industry product, but as a value-oriented cultural praxis. This study aims to examine the urgency of an axiological approach to art development and to formulate a conceptual framework that positions ethical, aesthetic, social, and spiritual values as its normative foundation. A qualitative descriptive design was employed using library research through a critical review of literature on the philosophy of science, philosophy of art, and critical social theory. The findings indicate that without a clear axiological foundation, art risks being reduced to an economic instrument, thereby losing its reflective, critical, and emancipatory functions. The study proposes four integrated axiological dimensions for art development: (1) the aesthetic-reflective dimension, which views art as a transformative and reflective experience; (2) the ethical dimension, emphasizing moral responsibility in artistic practice; (3) the social-communicative dimension, positioning art as a medium for dialogue, cultural interaction, and social criticism; and (4) the spiritual-existential dimension, which regards art as a means of seeking meaning and promoting human flourishing. These dimensions reinforce the role of art as a value-based social praxis that fosters critical awareness and supports the sustainability of human values. This framework contributes to the philosophy of art by providing a normative reference for artistic practice, cultural policy, and future studies grounded in humanistic values.